(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Prolegomena - 2. Princìpi ispiratori - 3. Gli organi giudiziari: a) il Tribunale e la Corte di Appello - 4. Segue: b) la Corte di Cassazione - 5. Gli avvocati - 6. L’organizzazione degli uffici giudiziari - 7. Annotazioni conclusive. Considerations on the new judicial system of the Vatican City State ABSTRACT: Law 16 March 2020 n. CCCLI upon the Vatican judiciary system is an important part of the reform process underway for twenty years, to adapt the Vatican State’s legal system to the needs of the historical moment. The reform examined responds to the highest levels of protection required by the "fair trial" and to the need to harmonize the Vatican system with the norms contained in international conventions signed by the Holy See. The essay critically examines the fundamental points of the reform.